Pengaruh Uang Saku, Lingkungan Sosial dan Locus of Control Terhadap Perilaku Keuangan dengan Financial Technology Sebagai Variabel Intervening - Puspitasari, Kristina Indah; Sriyono; Herlinda Maya Kumalasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of Pocket Money, Social Environment and Locus of Control on Financial Behavior with Financial Technology as an Intervening Variable. The research method in this study uses quantitative research methods with primary data sources obtained by distributing questionnaires. Sampling was carried out using probability sampling and resulted in 100 student respondents. Data analysis techniques use SmartPLS4. The research results show that: (1) Pocket Money has no effect on Financial Technology (2) Social Environment has an effect on Financial Technology (3) Locus of Control has an effect on Financial Technology (4) Pocket Money has no effect on Financial Behavior (5) Social Environment has an effect on Financial Behavior (6) Financial Technology influences Financial Behavior (7) Locus of Control influences Financial Behavior (8) Financial Technology cannot be an intermediary for Pocket Money in influencing Financial Behavior (9) Financial Technology cannot be an intermediary for the Social Environment in influencing Financial Behavior (10) Financial Technology cannot be an intermediary for Locus of Control in influencing Financial Behavior.